Global, regional, and national burden of NAFLD in youths and young adults aged 15–39 years, 1990–2021, its attributable risk factors, and projections to 2035: a systematic analysis of the Global Burden of Disease Study 2021 - Wang, Jiong; Du, Jiqing; Wang, Minxiu; Jin, Mengyun; Tang, Zhihua; Mao, Yuqin (Frontiers in Nutrition, 2025)
Non-alcoholic fatty liver disease (NAFLD) is a significant health burden in youths and young adults, and the trend toward younger onset of NAFLD is alarming. Utilizing data from the Global Burden of Disease (GBD) 2021 study, this study assessed the burden and trends of NAFLD in youths and young adults aged 15–39 from 1990 to 2021 and extracted data from this study on the incidence, prevalence, death, and disability-adjusted life-years (DALYs) rates of NAFLD. We evaluated the global temporal trend of NAFLD from 1990 to 2021 with estimated annual percentage change (EAPC) and age-standardized rate (ASR). The Bayesian age-period-cohort (BAPC) model was used to predict future trends of the NAFLD burden to 2035. We found that the global burden of NAFLD in youths and young adults has risen steadily from 1990 to 2021, and projects to increase to 2035, which places enormous pressure on society. To alleviate this burden, implementing measures targeting risk factors such as glycemic control and smoking cessation is necessary.